The right to housing in the context of the covid-19 pandemic (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
This article investigates the effects of the COVID-19 pandemic on the right to housing, especially for the low-sufficient. The importance of guaranteeing the fundamental and social right to housing, provided for in art. 6 of the Federal Constitution, even more in the pandemic context we are experiencing. One of the main ways to control the dissemination of the coronavirus is the need for social isolation and staying at home, which is why the need to guarantee decent housing was even more emphasized. For no other reason, greater legal protection is needed for this right, so dear to the poorest and intrinsically linked to the dignity of the human person. The Federal Supreme Court was asked to comment on the subject and established, albeit in an injunction, guidelines for the protection of housing and health in the context of the COVID-19 pandemic. The methodology was based on a literature review and a study of jurisprudence.